Nosocomial cutaneous abscesses in septic infants. Issue 2 (1st March 2004) - Mandel, D; Littner, Y; Mimouni, F B; Dollberg, S
Abstract : Objective: To retrospectively study the epidemiology of nosocomial cutaneous abscesses in 46 consecutive septic infants. Results: Ten infants had one abscess or more. Surviving infants with abscesses had a longer duration of bacteraemia, which disappeared within 24 hours of drainage. Conclusion: Infants with persistent bacteraemia should be examined regularly for the presence of abscesses.